2011
DOI: 10.1038/tp.2011.47
|View full text |Cite
|
Sign up to set email alerts
|

BDNF polymorphism predicts the rate of decline in skilled task performance and hippocampal volume in healthy individuals

Abstract: Numerous studies have indicated a link between the presence of polymorphism in brain-derived neurotrophic factor (BDNF) and cognitive and affective disorders. However, only a few have studied these effects longitudinally along with structural changes in the brain. This study was carried out to investigate whether valine-to-methionine substitution at position 66 (val66met) of pro-BDNF could be linked to alterations in the rate of decline in skilled task performance and structural changes in hippocampal volume. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 70 publications
2
36
0
Order By: Relevance
“…Age magnification of the effects of BDNF has also been reported for other measures of brain integrity, emphasizing the role of BDNF in modulating myelin expression [40] and survival of neurons in the adult brain [41]. Specifically, Met carriers had lower hippocampal volumes than Val homozygotes after age 65, whereas no such differences were apparent at younger ages ( Figure 3C) [38]. Crucially, age was unrelated to hippocampal volume in Val homozygotes, supporting the idea that brain maintenance in old age may partly reflect genetic factors [4].…”
Section: Trends In Cognitive Sciencesmentioning
confidence: 79%
See 2 more Smart Citations
“…Age magnification of the effects of BDNF has also been reported for other measures of brain integrity, emphasizing the role of BDNF in modulating myelin expression [40] and survival of neurons in the adult brain [41]. Specifically, Met carriers had lower hippocampal volumes than Val homozygotes after age 65, whereas no such differences were apparent at younger ages ( Figure 3C) [38]. Crucially, age was unrelated to hippocampal volume in Val homozygotes, supporting the idea that brain maintenance in old age may partly reflect genetic factors [4].…”
Section: Trends In Cognitive Sciencesmentioning
confidence: 79%
“…In addition, in line with the resource-modulation hypothesis, longitudinal data from a sample of older adults aged 70 to 103 years demonstrate exacerbated decline in perceptual speed across 13 years for Met carriers [37], an effect that remained after excluding prodromal dementia cases ( Figure 3A). Similarly, pilots carrying the Met allele (aged 40-69 years) declined disproportionately across 2 years in flight-simulator performance, presumably reflecting executive functioning [38]. At the neural level, BDNF Met carriers exhibited lower hippocampal activity during encoding and retrieval of episodic memories [35].…”
Section: Trends In Cognitive Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in line with the resource modulation hypothesis, longitudinal data demonstrate exacerbated decline in perceptual speed across 13 years among BDNF Met carriers (Ghisletta et al 2014), an effect that remained after excluding prodromal dementia cases. Similarly, Sanchez et al (2011) reported that pilots carrying the Met allele (aged 40-69 years) declined disproportionately in flight-simulator performance, presumably reflecting executive functioning.…”
Section: Bdnf Polymorphismmentioning
confidence: 99%
“…Cross-sectional imaging studies have shown age magnification of the effects of BDNF for grey-matter volumes (Sanchez et al 2011) and white-matter microstructure (Kennedy et al 2009). Specifically, Met carriers had lower hippocampal volumes than Val homozygotes after age 65, whereas no such differences were apparent before 65 years (Sanchez et al 2011). Critically, age was uncorrelated with hippocampal volume in Val homozygotes, supporting the idea that brain maintenance in old age may be partly due to genetic factors .…”
Section: Bdnf Polymorphismmentioning
confidence: 99%